Pricing practices for scientific products - Klymentova, M. V.; Kobielieva, T. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
A methodology has been developed for establishing competitive prices for high-tech innovative products that are adequate to market conditions.
Практика ціноутворення на наукову продукцію
Keywords: prices; scientific products; market; demand; supply; intellectual property